Estudios de coordinación de las protecciones por métodos computarizados aplicados a la central térmica trinitaria - Aguirre Marrett, Pedro Roberto (2013)
This study deals with the analysis of the electrical system of the Electrical Thermal Trinitaria of the study Power Flow to determine the current state of Guayaquil system and verify that the generator is capable of supplying the entire load connected to its bar without the contribution of the National Interconnected system SNI, in addition, the study was conducted to know the short-circuit current fault maximum and minimum flowing through the electrical system in order to determine the correct setting of the Central electrical protection which is checked with data taken from the information provided by the areas of operation and maintenance of the plant